2018
DOI: 10.21608/omx.2018.5623
|View full text |Cite
|
Sign up to set email alerts
|

Plate-related complications after mandibular reconstruction: observational study osteotomy

Abstract: Background: Mandibular reconstruction following bony resection is crucial in cases of oral and mandibular tumors. Complications such as infection, plate exposure, or plate fracture can occur because of some risk factors after these reconstructive surgeries. Objectives: The purpose of this study were to report some of the postoperative complications of reconstruction plates, and to analyze the risk factors associated with those complications. Patients and methods:We analyzed clinical and radiological data of 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…With this study, possible risk factors could be identified showing a significant correlation with the occurrence of complications in general, and especially with infections and infections with problematic germs. The complication rate of 25.8% in the cohort is in the lower to medium range of the 10.3 to 69.2% reported as having a high variability by comparable studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Regarding our complication rate, the fact should be considered that we have only recorded complications that required a surgical revision procedure after bone reconstruction and augmentation on the recipient side, and that we did not assess donor site morbidity including wound healing complications such as those observed rather frequently after skin-split grafts at the donor site.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…With this study, possible risk factors could be identified showing a significant correlation with the occurrence of complications in general, and especially with infections and infections with problematic germs. The complication rate of 25.8% in the cohort is in the lower to medium range of the 10.3 to 69.2% reported as having a high variability by comparable studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Regarding our complication rate, the fact should be considered that we have only recorded complications that required a surgical revision procedure after bone reconstruction and augmentation on the recipient side, and that we did not assess donor site morbidity including wound healing complications such as those observed rather frequently after skin-split grafts at the donor site.…”
Section: Discussionmentioning
confidence: 63%
“…The choice of graft depends on the anatomical location and size of the defect, with fibula grafts being the most used as the current "gold standard" [1,2]. The complication rate for reconstruction and augmentation procedures using autologous bone grafts in craniofacial surgery is reported with a greatly varying range between 10.3 to 69.2% [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], a re-operation rate of 10.6 to 58.2% [11,[18][19][20][21] and a graft failure rate of 1.3 to 27% [3,[9][10][11]13,[20][21][22]. The correlation between graft failure and complication rate is controversially discussed with the type of graft used [2,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of mandibular reconstruction has improved greatly in recent years due to the use of titanium reconstruction plates that provide better biocompatibility and locking screws for biomechanical enhancement. These improvements effectively provide rigid fixation needed for proper bone healing [ 14 ]. A 10-year review by Ellis et al found that in cases of comminuted mandibular fractures, ORIF with a bone reconstruction plate had low complication rates [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This bone graft is commonly harvested from the iliac or tibia, processed in a particulate form, and inserted into the body using an implant, typically made from titanium. However, serious problems such as implant fractures during the healing phase are still encountered (Martola et al, 2007;Radwan & Mobarak, 2018;Seol et al, 2014;Yamada et al, 2016). Almansoori et al (2020) reported that implant fractures were observed in 13.84% of mandibular reconstruction cases.…”
Section: Introductionmentioning
confidence: 99%